Type tricks your personal guide to type design - Beier, Sofie (BIS Publishers, 2017)
Type Tricks' is about typographical rules and the underlying structure of the work process in the design of new typefaces. In that way, it is both a reference book and a user manual. In an illustrative format, it presents the different stages of type design in an easily accessible manner.